Small-scale multilingualism through the prism of lexical borrowing. (August 2021) - Chechuro, Ilia; Daniel, Michael; Verhees, Samira
Aims and Objectives: We assess whether data on lexical borrowing obtained through field elicitation may point not only to a specific donor language but also to its specific regional variety, and whether these data are a reliable tool for reconstructing unknown historical patterns of interaction between ethnic subgroups. Methodology: We use quantitative analysis of the data obtained by loanword probing—elicitations of short wordlists from speakers of minority languages—to calculate the amount and identify the source of lexical transfer. We compare the results across several areas with varying degrees of bilingualism and different contact varieties of the donor language to see how this influences our results. Data: The data for this study come from a large-scale field study in Daghestan, with 72 people from 19 villages speaking four languages. Findings: Our method suggests that speech communities clearly indicate one of the regional varieties of Azerbaijani as the donor, depending on the area of data collection. We also observe that the degree of lexical convergence with the donor depends not only on the level of bilingualism observed in the specific village but also on the native language of this village, suggesting language borders as a natural constraint to the spread of lexical borrowing. Originality: The study is novel in that it is fully based on analysis of data on lexical convergence obtained through fieldwork on minority languages and provides quantitative results that can be compared across speech communities in the survey. Implications: We conclude that the method is sensitive enough to trace donorship to specific regional varieties of the donor language. Limitations: Our observations on the relative weight of the level of bilingualism and language affiliation of a speech community as predictors of the degree of lexical convergence require more data obtained both from other linguistic environments and by different methods.